Fed–batch fermentation of onion vinegar using Acetobacter tropicalis - Lee, Sulhee; Jang, Jae Kweon; Park, Young–Seo (Food science and biotechnology, 2016)
To produce onion vinegar with high efficiency, various fermentation conditions, such as varying initial ethanol concentrations and the addition of ethanol or onion juice were optimized. Acetobacter tropicalis KFCC 11476P consumed ethanol at a rate of 0.125–0.140 g/h when the initial ethanol concentrations were 4, 5, and 6%, and the acidity of the fermentation broth reached the maximum level when the ethanol was completely starved. In the case of fed-batch fermentation with continuous feeding, when a small amount of ethanol and onion juice was continuously supplied into the broth after 30 h of fermentation, the acidity continued to increase up to 4.5% at 45 h. All the while, the remaining ethanol content of the fermentation broth was 1.13-1.69%. The maximum acidity of onion vinegar in the pilot–scale fermenter reached 4.6% at 48 h of which fermentation speed was five times faster than the general standard.